2013
DOI: 10.1007/s11255-013-0549-1
|View full text |Cite
|
Sign up to set email alerts
|

QT dispersion predicts mortality and correlates with both coronary artery calcification and atherosclerosis in hemodialysis patients

Abstract: QTcd independently predicted mortality, and it was significantly associated with coronary artery calcification, left ventricular hypertrophy and atherosclerosis in HD patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 26 publications
1
5
0
Order By: Relevance
“…The link between LVH and prolonged QT found in HD patients in the present study has previously been demonstrated by a number of authors in patients with hypertension and hypertrophic cardiomyopathy 13 and also in HD patients. 21 , 23 , 24 However, the correlation between QTcd and LVH in HD patients is uncertain with some studies reporting positive correlation 14 , 21 , 24 and others, corroborating our findings, absence of correlation between these variables. 22 , 30 The current review of literature on the electric heterogeneity in LVH allows us to conclude that electrical disturbances do indicate ventricular structural abnormalities.…”
Section: Discussionsupporting
confidence: 86%
“…The link between LVH and prolonged QT found in HD patients in the present study has previously been demonstrated by a number of authors in patients with hypertension and hypertrophic cardiomyopathy 13 and also in HD patients. 21 , 23 , 24 However, the correlation between QTcd and LVH in HD patients is uncertain with some studies reporting positive correlation 14 , 21 , 24 and others, corroborating our findings, absence of correlation between these variables. 22 , 30 The current review of literature on the electric heterogeneity in LVH allows us to conclude that electrical disturbances do indicate ventricular structural abnormalities.…”
Section: Discussionsupporting
confidence: 86%
“… 6 , 9 Recent literature suggests that various ECG changes, such as prolonged PR, QRS, or QTc intervals, may be independent risk predictors for cardiovascular (CV) death in patients with chronic kidney disease. 10 - 12 …”
Section: Introductionmentioning
confidence: 99%
“…Further attempts to characterize this relationship have focused on QT dispersion, an electrocardiographic index that is generally higher in the dialysis population, and which correlates with risk for sudden cardiac death . At least three studies have found that QT dispersion significantly increases immediately after a dialysis session, when Mg fluxes would be expected to be greatest.…”
Section: Magnesium and Sudden Cardiac Deathmentioning
confidence: 99%